Assessment of the healing properties of Cichorium intybus L. extracts on wounds - Berivan Kaçmaz; Duygu Misirli; Seçil Erden Tayhan; Zafer Ömer Özdemir; Mahfuz Elmastaş (Phytomedicine Plus)
Background: Throughout the course of an individual's lifespan, they may come across a diverse range of minor or significant incidents that have the potential to result in the development of scars on any region of their physique. These scars may also be a consequence of the body's innate responses to different stimuli. Various medicinal drugs and methods have been used to treat scars. Herbal remedies have long been popular. Cichorium intybus L., or chicory, has been used for centuries to treat numerous illnesses and deformities. Purpose: The primary objective and novelty of this research endeavor involve the investigation of potential therapeutic attributes inherent in extracts derived from different components of C. intybus (common chicory), encompassing the root, stem, flower, and whole herba. This will be accomplished through the utilization of in vitro scratch tests and in vitro cell migration assays. Additionally, the ash acquired from cremation, a method routinely employed by the general population, was also investigated. Study design: The focus of this investigation was to evaluate the wound healing effects of these extracts. The research encompassed a comprehensive examination of several components of the plant in order to ascertain the extracts that exhibited the highest efficacy. Methods: The study utilized the following approaches respectively to investigate the plant's wound healing abilities: collection and identification of plants, preparation of extracts, determination of phenolic compounds by HPLC-PDA, in vitro cell culture studies, cell viability analysis, wound healing analysis, statistical analysis. Results: The findings indicated that the stem extracts of C. intybus, with the exception of the hexane extract (Sample 1), demonstrated notable wound healing properties. According to the chromatography results the main component of extract is chlorogenic acid. The aforementioned findings offer significant contributions to the potential directions for future research within this particular sector. Conclusion: The evidence suggests that extracts from C. intybus have wound healing properties, highlighting its significance in traditional medicine and pharmaceutical research. Further investigation into active chemicals and mechanisms contributing to its wound healing properties is needed, potentially leading to advancements in wound healing therapies.